2D Palladium Sulphate for Visible‐Light‐Driven Optoelectronic Reversible Gas Sensing at Room Temperature. Issue 3 (8th December 2021) - Alkathiri, Turki; Xu, Kai; Zhang, Bao Yue; Khan, Muhammad Waqas; Jannat, Azmira; Syed, Nitu; Almutairi, Ahmed F. M.; Ha, Nam; Alsaif, Manal M. Y. A.; Pillai, Naresha; Li, Zhong; Daeneke, Torben; et al.
Abstract : 2D metal sulphides (MSs) have attracted enormous amounts of attention in developing high‐performance gas sensors. 2D noble metal sulphides and their derivatives, however, have been less studied due to their predominant nonlayered crystal structures for inefficient exfoliation, despite their surface and peculiar optoelectronic properties. Herein, we successfully synthesize 2D palladium sulphate (PdSO4 ) from palladium sulphide (PdS) bulk crystals by liquid‐phase exfoliation, in which the presence of oxygen species in the exfoliation solvent plays a key role in the sulphate transformation. Ultrathin 2D PdSO4 planar nanosheets, with thicknesses of ≈3 nm and submicrometer lateral dimensions, exhibit a broad absorption across the visible spectrum, a narrow bandgap of ≈1.35 eV, and a nanosecond scaled long exciton lifetime, which are all suitable for the visible‐light‐driven optoelectronic gas sensing applications. The 2D PdSO4 ‐based sensor demonstrates a reversible, selective, and sensitive response toward ppb‐leveled NO2 gas at blue light irradiation, featuring a response factor of ≈3.28% for 160 ppb NO2, a low limit of detection of 1.84 ppb, and a > 3 times response factor enhancement over other gases. Herein, the possibility of realizing 2D ultrathin noble metal sulphide compounds from their nonlayered crystal structures and strong potentials in developing high‐performance chemical sensors is explored. Abstract : 2D palladium sulphate (PdSO4 ) nanosheets have successfully been delaminated from palladium sulphide bulk crystals utilizing liquid‐phase exfoliation featuring sub‐micron lateral dimensions, nano‐scale thicknesses, and a narrow bandgap. Upon blue light irradiation, 2D PdSO4 ‐based sensor exhibits reversible, selective, and sensitive responses toward nitrogen dioxide (NO2 ) gas with a response factor of 3.28% for 160 parts per billion (ppb).